Peltigera frigida Lichens and Their Substrates Reduce the Influence of Forest Cover Change on Phosphate Solubilizing Bacteria - Muster, Cecilia; Leiva, Diego; Morales, Camila; Grafe, Martin; Schloter, Michael; Carú, Margarita; Orlando, Julieta (Frontiers in Microbiology, 2022)
Phosphorus (P) is one of the most critical macronutrients in forest ecosystems. More than 70 years ago, some Chilean Patagonian temperate forests suffered wildfires and the subsequent afforestation with foreign tree species such as pines. Since soil P turnover is interlinked with the tree cover, this could influence soil P content and bioavailability. Next to soil microorganisms, which are key players in P transformation processes, a vital component of Patagonian temperate forest are lichens, which represent microbial hotspots for bacterial diversity. In the present study, we explored the impact of forest cover on the abundance of phosphate solubilizing bacteria (PSB) from three microenvironments of the forest floor: Peltigera frigida lichen thallus, their underlying substrates, and the forest soil without lichen cover. We expected that the abundance of PSB in the forest soil would be strongly affected by the tree cover composition since the aboveground vegetation influences the edaphic properties; but, as P. frigida has a specific bacterial community, lichens would mitigate this impact. Our study includes five sites representing a gradient in tree cover types, from a mature forest dominated by the native species Nothofagus pumilio, to native second-growth forests with a gradual increase in the presence of Pinus contorta in the last sites. In each site, we measured edaphic parameters, P fractions, and the bacterial potential to solubilize phosphate by quantifying five specific marker genes by qPCR. The results show higher soluble P, labile mineral P, and organic matter in the soils of the sites with a higher abundance of P. contorta, while most of the molecular markers were less abundant in the soils of these sites. Contrarily, the abundance of the molecular markers in lichens and substrates was less affected by the tree cover type. Therefore, the bacterial potential to solubilize phosphate is more affected by the edaphic factors and tree cover type in soils than in substrates and thalli of P. frigida lichens. Altogether, these results indicate that the microenvironments of lichens and their substrates could act as an environmental buffer reducing the influence of forest cover composition on bacteria involved in P turnover.